Establishing and expanding the private sector land development industry in Greater Kathmandu, Nepal - Karki, Tej Kumar; Archer, Ray W.; Kammeier, Hans Detlef; Lefebvre, Bernard G.; Canadian International Development Agency, Broad Based Development Programme (CIDA- BBDP) (Bangkok : Asian Institute of Technology, 1991)
Due to the rapid urbanization, the Kathmandu and Lalitpur urban areas astride the Bagmati River have merged into Greater Kathmandu. In 1981, the population of Greater Kathmandu was about 316000 persons and in 1991 it reached 592900 by an average exponential growth rate of 3.8 I. per annum. The urban growth of Greater Kathmandu is mainly by its outward expansion through land development in the fringe areas which is mainly undertaken by land brokers. However, their system of parcel by parcel land partitioning is inefficient for land use and is scattered in location. Also their formation of meandering lanes of varying width has caused serious problems of vehicular access and surface water drainage. Government land development projects have failed to provide adequate land supply for housing due to various constraints. Hence, to solve these problems, there is need to improve private land development by undertaking properly layout subdivision projects and by assembling larger area of land for project sites which could be designed into layouts of regular plots a nd desirable access roads. Some of the l and developers and land brokers have commenced a few such land subdivision projects but they have not yet been able to expand this activity to respond to the demand for land for housing. This research mainly focusses on the land development activities of these brokers and the land development companies in an attempt to understand the various impediments to the expansion of the infant l a nd development industry so as to undertake more and better l and subdivision projects. Some 16 land brokers and 1 7 land developers of the different companies were interviewed. Some of the land subdivision projects of the land development companies and the l and· development cooperatives were studied during the field study, as well as an apartment development project. In order to improve the private l and development system, the study recommends amendments to the land acts, the provision of credit finance , assisting the private l and assembly process, training for skill in l and subdivision, access to construction equipment for network infrastructure works, government extension of the network infrastructure to the fringe lands, modernisation of the official land records, improvement of the cadastral mapping system, and a land information system. The study also recommends exemptions from the l and registration tax, a guarantee or support for private land purchase agreements, and the adopt ion of minimum land subdivision regulations. These measures should be undertaken by the government to assist and guide the emerging private l and developers, both l and brokers and land development companies.
A thesis submitted in partial fulfillment of the requirements for the award of the Degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1991
Keywords: Real estate development -- Nepal -- Kathmandu